1992
DOI: 10.1093/ajcn/56.2.320
|View full text |Cite
|
Sign up to set email alerts
|

Effects of weight reduction on blood lipids and lipoproteins: a meta-analysis

Abstract: Studies designed to examine effects of weight reduction by dieting on total cholesterol (TC), low-density-lipoprotein cholesterol (LDL-C), high-density-lipoprotein cholesterol (HDL-C), very-low-density-lipoprotein cholesterol (VLDL-C), and triglycerides (TGs) have reported inconsistent results. The purpose of this study was to quantify effects of weight loss by dieting on lipids and lipoproteins through the review method of meta-analysis. Results from the 70 studies analyzed indicated that weight reduction was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

43
447
13
37

Year Published

1996
1996
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 918 publications
(540 citation statements)
references
References 83 publications
43
447
13
37
Order By: Relevance
“…The magnitude of these changes per kilogram of weight loss is similar to earlier findings; 34 however, the largest change occurred within 4 wk of commencing the diet, suggesting that dietary lipid profile and/or ER have a greater impact than total weight loss. Indeed, previous studies have shown that HP diets improve plasma lipid profile in the absence of weight loss.…”
Section: Discussionsupporting
confidence: 86%
“…The magnitude of these changes per kilogram of weight loss is similar to earlier findings; 34 however, the largest change occurred within 4 wk of commencing the diet, suggesting that dietary lipid profile and/or ER have a greater impact than total weight loss. Indeed, previous studies have shown that HP diets improve plasma lipid profile in the absence of weight loss.…”
Section: Discussionsupporting
confidence: 86%
“…Fourth, greater weight reduction in the vegetarian groups was found compared with omnivorous groups (−2.88 kg, 95% CI −3.56 to −2.20, P <0.001) (Figure 5). Weight reduction was significantly associated with decrease of TC and LDL‐C50; therefore, some of the effect of the change in TC and LDL‐C in this meta‐analysis could be a consequence of weight loss. Fifth, our analysis covers a long time span of 30 years, with the oldest study performed in 1982 and the latest trial conducted in 2013.…”
Section: Discussionmentioning
confidence: 79%
“…Also, weight regain will be undetected in short-term studies because it occurs slowly in over 80% of people who lose weight. 2,19,20 Clinically important weight loss, defined by obesity experts as loss of 5-10% of baseline weight, [21][22][23][24] may improve lipid, glucose, and blood pressure levels, [25][26][27] with potential reductions in cardiovascular disease. [28][29][30] However, it is unclear if weight loss improves risk factors in all obese persons or only in high-risk groups.…”
Section: Introductionmentioning
confidence: 99%